The Göppingen confession - Bèze, Théodore de (Reformation & Renaissance review, 2016)
"The text of the Farel -Beza Confession on the Eucharist, presented at Göppingen, 14 May 1557, from the Latin text original in CO 16, cols. 469-72, no. 2628"